Carrier type affects anammox community assembly, species interactions and nitrogen conversion. (February 2023) - Zhang, Baoyong; Zhang, Nianbo; He, Ao; Wang, Chen; Li, Zhen; Zhang, Guanjun; Xue, Rong
Graphical abstract: Highlights: Carrier type imposed selection pressure on microbial recruitment. Elastic cubic sponges induced closer cooperation within anammox community. Carrier type affected nitrogen conversion related enzymes and genes abundances. Elastic cubic sponges improved biofilm activity, EPS and heme c content. Abstract: The impacts of carrier type on anammox community assembly, species interactions and nitrogen conversion were studied in this work. It was found that in addition to shared species with higher abundance, different carrier types recruited rare species by imposing selection pressure. Results from co-occurrence networks revealed that carrier type strongly influenced interactions between keystone species inhabiting within anammox biofilm through potentially inducing niche differences. Overall, elastic cubic sponges would lead to closer cooperation between different populations, whereas plastic hollow cylinders would trigger fiercer competition. Meanwhile, the results based on metagenomics sequencing showed carrier type significantly affected nitrogen conversion related genes abundances, and higher reads number was detected on the elastic cubic sponges. The information obtained in this work could provide some valuable information for the selection and optimization of carrier type in the anammox process.